Dampak Sistem Komandante Stelsel oleh DPD PDI Perjuangan Jawa Tengah terhadap Keterpilihan Calon Anggota DPRD Jawa Tengah - Alan Bayu Aji (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
In the 2024 General Election, DPD PDI Perjuangan Central Java implemented the Komandante Stelsel system to win DPRD seats through gotong royong. If a candidate gets the most votes but is not from the designated ampuan area, the candidate must resign and be replaced by another candidate according to this system. This research examines the rules for the election of DPRD candidates in the 2024 elections and the impact of the Komandante Stelsel system implemented by the DPD PDI Perjuangan Central Java. The research method uses empirical approach, case study, and legislation. The results showed that the 2024 Election uses an open proportional system, where the electability of candidates is based on the most votes. However, the Komandante Stelsel system is different because candidates' valid votes can only be obtained from the ampuan region. As a result, many candidates who obtained the most votes failed to become DPRD members because they had to resign in accordance with the provisions of this system.